The Effectiveness of QuillBot in Enhancing English Writing Skills - Nugroho, Prasetyo Eka; Ilham, Ilham; Irwandi, Irwandi; Lukman, Lukman (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the effectiveness of QuillBot, an AI-based writing tool, in enhancing the English writing skills of EFL students at Universitas Muhammadiyah Mataram. Using a pretest–posttest design with a quantitative approach, the research involved a sample of 15 students who received training in utilizing QuillBot for academic writing tasks. Students’ writing performance was assessed before and after a four-week intervention. The results demonstrated a significant improvement, with the average score increasing from 56.73 in the pretest to 75.67 in the posttest. These findings suggest that QuillBot effectively improves writing quality, particularly in grammar, vocabulary, and cohesion. However, the study did not compare QuillBot with other AI tools, nor did it explore its broader impact on motivation or critical thinking. Future research is recommended to conduct comparative studies and to investigate the long-term implications of AI integration in language learning.